Designing Promotion Strategy of Malang Raya's Tourism Destination Branding through Audio Visual Media - Nuansa, Chanira; Suryadi, Suryadi; Wisadirana, Darsono (Journal of Indonesian Tourism and Development Studies, 2014)
This study examines the suitability concept of destination branding with existing models of Malang tourism promotion. This research is qualitative by taking the data directly in the form of existing promotional models of Malang, namely: information portal sites, blogs, social networking, and video via the Internet. This study used SWOT analysis to find strengths, weaknesses, opportunities, and threats on existing models of the tourism promotion. The data is analyzed based on destination branding's concept indicators. Results of analysis are used as a basis in designing solutions for Malang tourism promotion through a new integrated tourism advertising model. Through the analysis we found that video is the most suitable media that used to promote Malang tourism in the form of advertisements. Videos are able to show the objectivity of the fact that intact better through audio-visual form, making it easier to associate the viewer thoughts on the phenomenon of destination. Moreover, video creation of Malang tourism as well as conceptualized ad is still rare. This is an opportunity, because later models of audio-visual advertisements made of this study is expected to be an example for concerned parties to conceptualize the next Malang tourism advertising. Keywords: Advertise, SWOT Analysis, Malang City, tourism promotion